(x+19)2(x+19)^{2} - (x19)2(x-19)^{2}

asked by guest
on Jan 29, 2025 at 11:46 am



You asked:

Evaluate the expression: (x+19)2(x19)2{\left( x + 19 \right)}^{2} - {\left( x - 19 \right)}^{2}

MathBot Answer:

Evaluated



(x+19)2(x19)2=(x19)2+(x+19)2\displaystyle {\left( x + 19 \right)}^{2} - {\left( x - 19 \right)}^{2} = - \left(x - 19\right)^{2} + \left(x + 19\right)^{2}


Expanded

(x+19)2(x19)2=76x{\left( x + 19 \right)}^{2} - {\left( x - 19 \right)}^{2} = 76 x


Factored

(x+19)2(x19)2=76x{\left( x + 19 \right)}^{2} - {\left( x - 19 \right)}^{2} = 76 x